2013
DOI: 10.1590/s0100-736x2013001200005
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de anticorpos IgG anti-Trypanosoma vivax em bovinos através do teste de Imunofluorescência indireta

Abstract: RESUMO.-Trypanosoma vivax infecta uma grande variedade de animais ungulados selvagens e domésticos, podendo causar grande impacto na produção de ruminantes. Este trabalho teve como objetivo avaliar a detecção de anticorpos IgG anti-Trypanosoma vivax em bovinos provenientes do estado de Pernambuco, Brasil. Para tanto, foram analisadas 2,053 amostras de soro sanguíneo de bovinos provenientes de rebanhos de municípios do estado de Pernambuco, os quais foram analisados através da Reação de Imunofluorescência Indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(18 reference statements)
1
9
0
2
Order By: Relevance
“…True prevalence rate of T. vivax at individual level was 9.9%, similar to the rate found in the first and only outbreak of trypanosomiasis by T. vivax reported in Minas Gerais so far (7.4%) on a dairy farm in Igarapé, metropolitan mesoregion of Belo Horizonte (15) , and below the rate found in Pernambuco, 14% (8) . However, prevalence rates of 30.7-93.1% are not uncommon in Brazilian endemic areas such as Pantanal and North Region (9,39,40) , well above those reported in Southern Minas Gerais.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…True prevalence rate of T. vivax at individual level was 9.9%, similar to the rate found in the first and only outbreak of trypanosomiasis by T. vivax reported in Minas Gerais so far (7.4%) on a dairy farm in Igarapé, metropolitan mesoregion of Belo Horizonte (15) , and below the rate found in Pernambuco, 14% (8) . However, prevalence rates of 30.7-93.1% are not uncommon in Brazilian endemic areas such as Pantanal and North Region (9,39,40) , well above those reported in Southern Minas Gerais.…”
Section: Discussionsupporting
confidence: 80%
“…For about two decades, this parasite was restricted to the North region, also occurring in the state of Amapá (5) . However, further outbreaks of bovine trypanosomiasis caused by T. vivax were confirmed in the North (6) , Northeast (7,8) , Midwest (9,10) , Southeast (11,12) , and South (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Most reports relate to isolated outbreaks, in which T. vivax acutely affects cattle, manifested by high parasitemia associated with clinical signs such as fever, anorexia, weight loss, sudden drop in milk production, abortion, and perinatal mortality. However, in the Northeast region of Brazil, the work carried out by GUERRA et al (2013) in cattle from herds of the municipalities of the state of Pernambuco found the prevalence of 13.93% (286/2053) of seropositive animals in the indirect immunofluorescence reaction.…”
Section: Discussionmentioning
confidence: 98%
“…The Northern region and the Mato Grosso Pantanal can be considered as enzootic stability for trypanosomiasis (GUERRA et al, 2013). Due to the abundance of mechanical vectors, most of the year, the animals develop active immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of the disease can be made by a combination of assessment of the clinical picture and parasitological, serological, and molecular techniques. In general, the diagnostic methods used to identify T. vivax are the detection of the hemoparasite by means of direct blood smear, serological assays such as indirect immunofluorescence assay (IFA) (Guerra et al, 2013), enzyme-linked immunosorbent assay (ELISA) ( et al, 2006), and molecular detection by polymerase chain reaction (PCR) (Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%